Are we intensifying the stigma? - Mitry, Caroline (AUC Knowledge Fountain, 2016)

(untitled)
This study analyzed the content of selected Egyptian movies that portrayed mental and psychological illness throughout the history of the Egyptian cinema between 1923 and 2015. A list that includes 42 movies depicting characters with mental or psychological illnesses was compiled, out of which 13 movies were selected for analysis. Selection criteria included: representation of the mental or psychological illness/disorder as the main character or issue around which the plot revolves, popularity of the leading actor or actress, and most importantly the significance of the movie in relation to the research questions of the study. Through content analysis of the selected movies, the study explored how they depicted individuals with mental or psychological illness, their characters, personality traits, their interaction with the society, and the nature of their relationship with their therapists (when applicable), exploring the cultural aspects and societal values within that context, in an attempt to explore that portrayal between 1923 and 2015. To further enhance the study, interviews with professionals in the media, film and psychology fields were conducted, to find out more about the representation of mental illness in the Egyptian cinema. Drawing on the media framing theory, the research questions pursued by this study examined the physical characteristics and character attributes as well as mental health indicators of mentally-ill individuals, as portrayed in Egyptian movies produced between 1923 and 2015. The study further attempted to look for the various connotations that the depictions of mental and psychological illnesses in Egyptian movies communicate about mental/psychological illness. Findings of the study revealed a generally negative portrayal of mental illness, labeling the mentally-ill as unacceptably different from other normal individuals in the society. Findings varied based on the movie genre; where comedy movies presented clearly exaggerated portrayals of various elements of mental illness, while drama ones presented more intense aspects, however still objectifying patients and reducing them to their illnesses.